Oral health status of 12-year-old children in Lisu minority ethnic group in China: a cross-sectional study - Kitty Jieyi Chen; Juan Liu; Biao Xu; Yuexiao Li; Yanhong Li; Shinan Zhang; Chun Hung Chu (BMC, 2021)
Abstract Background Lisu is an ethnic minority group and most of them are living in Yunnan, China. This study investigated the oral health status among 12-year-old Lisu children in Yunnan. Method This survey employed a multistage sampling method to recruit 12-year-old Lisu children. Two calibrated dentists performed the oral examinations in the primary schools. They examined dental caries, gingival bleeding and dental fluorosis using the diagnosis criteria recommended by the World Health Organization. A self-administrated questionnaire was distributed to the children to collect their sociodemographic background information and oral health-related behaviours. A chi-square test, the Mann-Whitney U test, zero-inflated negative binomial (ZINB) regression and multivariate logistic regression were used for statistical analysis. Results This survey invited 512 children, and 482 children (48% boys) participated in the study (response rate: 94%). Their caries prevalence was 35% and their caries experience in mean (SD) DMFT scores was 0.63 (0.10). The mean (SD) DT score was 0.60 (1.10), consisting 95% of the mean DMFT scores. No dental fluorosis was observed; whereas 426 children (88%) had gingival bleeding. Results of ZINB model indicated sex and sugary-snacking habits were related to the dental caries experience (p < 0.05). The gingival-bleeding prevalence was associated with the mother's education level, the child's monthly-pocket money and daily toothbrushing frequency (p < 0.05). Conclusion Dental caries and gingival bleeding were prevalent among 12-year-old Lisu children in the Yunnan province in China, and most of the decayed teeth were unrestored. Dental fluorosis was not observed in the children.